2017
DOI: 10.1093/fampra/cmx102
|View full text |Cite
|
Sign up to set email alerts
|

Using proton pump inhibitors correlates with an increased risk of chronic kidney disease: a nationwide database-derived case-controlled study

Abstract: Using PPIs presented 1.4-fold higher odds of CKD in Taiwan health insurance claims data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…Hung et al [16] claimed that the OR for CKD is 1.41 (CI 1.34, 1.48) for subjects using PPIs. Besides, the odds ratio of CKD in relation to the cumulative duration of different proton pump inhibitor is also clearly announced.…”
Section: Discussionmentioning
confidence: 99%
“…Hung et al [16] claimed that the OR for CKD is 1.41 (CI 1.34, 1.48) for subjects using PPIs. Besides, the odds ratio of CKD in relation to the cumulative duration of different proton pump inhibitor is also clearly announced.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that reported a weaker association of PPI use with CKD was conducted in Taiwan [ 13 ]. This large case-controlled study included 16,704 patients aged 20 or above and had been diagnosed with CKD.…”
Section: Resultsmentioning
confidence: 99%
“…Hypotheses generated from false associations can become a potential source of discontinuation of an established drug treatment. For example, two studies [ 12 , 13 ] included in the review only reported a weak association of CKD with the PPI use. Both weak as well as strong associations could be explained by the risk of confounding [ 21 ] and thus have limited merit in establishing causality when compared to RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…All comorbidities were diagnosed based on ICD-9 codes, which have been well assessed in previous studies. [2124]…”
Section: Methodsmentioning
confidence: 99%